INTERPRETATION OF DIAGNOSTIC TESTS IN CLINICAL EPIDEMIOLOGY - Bambang Sumiarto (Jurnal Sain Veteriner, 1998)
A test is process designed to detect a sign, substance tissue change, or response. The detection of signs or tissue abnormalities during [he diagnostic process, pregnancy diagnostic activities, and meat inspection findings, are also tests. Indeed, tests are used in virtually all problem solving activities and therefore the understanding of the principles of lest evaluation and interpretation are basic to many of practical veterinarian and researcher. Clinical epidemiology revolves around the use and interpretation of tests.